The Bank Lending Channel in Dual Banking Systems: How Market Power Shapes Monetary Policy Effectiveness - Kinan Salim; Moutaz Abojeib; Wajahat Azmi; Mhd Osama Alchaar (Jurnal Internasional Ekonomi Islam, 2023)
This paper investigates the effectiveness of the bank lending channel as a mechanism for monetary policy transmission in dual banking systems. Using generalized method of moments (GMM) estimators, we examine how market power and the presence of Islamic banks influence the bank lending channel. Our empirical results reveal that the effectiveness of this channel is conditional on the degree of market power. Specifically, we find that increases in interest rates are effective in altering bank lending only when the Lerner index, a measure of market power, reaches the threshold of 0.35. This suggests that the bank lending channel is only effective in markets with lower to average levels of competition (i.e. high market power). Additionally, we identify unique characteristics of Islamic banks that warrant further research for a comprehensive understanding of their role in the bank lending channel. Our study has important policy implications, particularly for emerging economies and dual banking systems, where regulatory measures may need to consider the intricate balance between market competition and effective monetary policy